Upaya Penurunan Persentase Rework pada UD. X - Felicia Fernanda; Felecia Felecia (Jurnal Titra, 2022)
UD. X is a company that manufacturing saws type bandsaw 44, 42, 36, 28, 2”, eva, sponge, bi-metal, horizontal, meatbandsaw, and scrollbandsaw. UD. X customers comes from various regions in Indonesia, like Medan, Ambon, Bali, Fak-Fak, Sorong, Manokwari, Bintuni, and Wasior. The obstacle is the percentage of rework in 2020 reached 5.79%. At UD. X all defective saws will be reworked which will delay the production schedule and deliveries. Therefore, this study is to reduce the percentage of rework using DMAIC. Pareto diagram shows there are three main types of defects, namely wave defects, thickened results, and thin joints. Cause-and-effect diagram shows that the cause is in man, method, and machine factors. There were five proposals made, four of them were successfully implemented, namely the manufacture of DRB, daily production boards, SOP, and track record of maintenance machines. One proposal that postponed is the manufacture of a joint thickness checking plate due to time constraints. After implementation, there was a decrease in the percentage of rework by 1.22% from January-December 2020, bringing the percentage of rework in November 2021 to 4.57%. Control efforts made include the use of daily production boards, monthly evaluations, utilization of track record, DRB, and SOP.